A conceptual approach to solving design problems using aspects of ethnic values - elements of a national costume, as a creative source for students in the «Costume Design» direction - Yeziyeva Z.M., Езиева З.М. (Рroblems of engineering and professional education, 2022)
The article defines the concept of «value», «ethnic values», emphasizes the importance of studying and creative processing of the national culture, which contributes to the enrichment and updating of the modern costume, the creation of a special national color in it. It is emphasized that the main value of a national costume is its ultimate functionality, the logic of forms and designs, rationality and expediency, and at the same time, in the variety of appearance options due to various decorative techniques. That is why among the sustainable styles in modern fashion, an ethnic style has established itself, the interest in which does not wane. The author hypothesizes that without a deep study of decorative arts, folk traditions, rites, customs, it is impossible to create a progressive modern costume. The relevance of the problem under consideration is determined by the formation of factors of ethnic values and the mechanisms of its impact when solving design problems using elements of the national costume as a creative source.